Effect Of Kerosene And Fuel Oil On Compressive Strength Of Reactive Powder Concrete (مجلة المنصور, 2022)
The aim of this study is to investigate the effect of two of oil products (kerosene and fuel oil which is locally called black oil) on compressive strength of reactive powder concrete. RPC was prepared using cement, silica fume, fine sand, steel fibers and superplasticizer to cast and test 63 specimens of cubes with various steel fibers ratios of 0%, 1% and 2% at different exposure periods in oil products (0, 30, 90 and 180) days. In general the results showed that RPC has good resistance to the effect of kerosene and fuel oil. A slight decrease in compressive strength occurred as the time of exposure to the oil products increase. The RPC specimens of2% steel fibers content had the lower decrease in compressive strength as a result of the denser microstructure. The decreasing ratio of RPC compressive strength exposed to fuel oil (1.33%)was lower than that of kerosene (2.91%). This may be attributed to the lower viscosity of kerosene than fuel oil.